Transferência internacional de tecnologia como mecanismo de difusão tecnológica: uma análise da economia brasileira a partir da abertura econômica da década de 1990 - Chagas, Valdinei Fernandes das (2022)
This dissertation analyzes some of the indicators of the process of technological innovation and diffusion (PTID) in the Brazilian economy, emphasizing the international transfer of technologies carried out by the country as one of the auxiliary instruments of economic development. Therefore, this research aims to identify the extent to which the acquired international transfer of technologies has contributed to the Brazilian PTID, considering that such flows are strategic and short-term alternative paths for breaking the economy's state of technological dependence and technological pairing in the long-term deadline. Since the economic opening up of Brazil in the 1990s, there is a theoretically favorable scenario for longterm economic growth and development, with expectations that external technologies will act as mechanisms for learning and internal development of the technologies themselves through reengineering, imitation and emulation. The approach based on neo-schumpeterian economic theory admits that technological innovations are one of the main instruments for promoting economic development, international competitiveness and economic pairing between countries. In this context, international transfers of technologies are a relevant instrument of analysis for understanding the PTID of the Brazilian economy, since the country has access to technology transfer channels. With this in mind, based on the PIDT model presented by Greenhalgh and Rogers (2010), which is subdivided into stages, indicators (scientific research, research & development, percentage of innovative companies, innovation rate, patents, exports of products and services with a high degree of technological intensity) referring to Brazilian data related to technological innovation, of which a theoretical-analytical examination was carried out, addressing the behavior and implications of the Brazilian economic trajectory in the 21st century, based on the implications of the “commercial opening” in the 1990s and considering the new techno-economic paradigm of “flexible technologies” — beneficial for the acquisition of foreign technologies, technological learning and international insertion. Based on the indicators, mainly on the technological balance of payments between the years 1993 and 2019, it was found that international transfers of technologies as a supporting mechanism for economic development are limited, given a structural sequence of technological deficits. Furthermore, the worsening bias of the technological deficits of the Brazilian economy can be noted, which represents technological dependence and the difficulties of generating technological surpluses — in short, international insertion and competitiveness — as well as economic pairing. Thus, the acquisition of external technologies has not worked, according to the neo-Schumpeterian literature, as an alternative short-term strategy for reversing technological backwardness and long-term economic development.